2019 9th International IEEE/EMBS Conference on Neural Engineering (NER) 2019
DOI: 10.1109/ner.2019.8717045
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Hand Kinematics from Local Field Potentials Using Long Short-Term Memory (LSTM) Network

Abstract: Local field potential (LFP) has gained increasing interest as an alternative input signal for brain-machine interfaces (BMIs) due to its informative features, long-term stability, and low frequency content. However, despite these interesting properties, LFP-based BMIs have been reported to yield low decoding performances compared to spike-based BMIs. In this paper, we propose a new decoder based on long short-term memory (LSTM) network which aims to improve the decoding performance of LFP-based BMIs. We compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 21 publications
(44 reference statements)
1
42
0
1
Order By: Relevance
“…In addition to θ, we also need to optimize the hyperparameters of DNNs, for which we employed the Bayesian optimization method (Ahmadi et al, 2019). To optimize the hyperparameters, we empirically preset the range for each parameter: the number of nodes in a layer ∈ {2 4 , 2 5 , .…”
Section: Deep Canonical Correlation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to θ, we also need to optimize the hyperparameters of DNNs, for which we employed the Bayesian optimization method (Ahmadi et al, 2019). To optimize the hyperparameters, we empirically preset the range for each parameter: the number of nodes in a layer ∈ {2 4 , 2 5 , .…”
Section: Deep Canonical Correlation Analysismentioning
confidence: 99%
“…The first category is a generative method that operates based on the generation of neuronal firing activities from kinematic states described by encoding models. The second category is a direct method that operates based on a direct input-output function approximation from neuronal firing activities to kinematic variables (Chapin et al, 1999;Sussillo et al, 2012;Dethier et al, 2013;Ahmadi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each LFP channel, six different features were extracted (one feature in the time domain and five features in the frequency domain). The time-domain feature was an average amplitude called local motor potential (LMP) whereas the frequency domain features were average spectral power in five different frequency bands: delta (1-4 Hz), theta (3-10 Hz), alpha (12-23 Hz), beta (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) and gamma (50-300 Hz). The selection of these frequency bands followed a previous study by Stavisky et al [2].…”
Section: Feature Extractionmentioning
confidence: 99%
“…LSTMs have demonstrated state-of-the-art performances in various applications such as language modelling and translation, speech recognition and synthesis, and video classification and captioning [29]. Our previous study has also shown that LSTM can achieve higher decoding performance when compared to a Kalman filter [30]. LSTM successfully addresses the vanishing gradient problem commonly encountered in traditional recurrent neural networks (RNNs) and is capable of learning long-term temporal dependencies.…”
Section: Feature Extractionmentioning
confidence: 99%